Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1073/pnas.85.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower mosaic virus gene VI produces a symptomatic phenotype in transgenic tobacco plants

Abstract: Gene VI of the cauliflower mosaic virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…The observation that the ability to cause rugosity, the only clear difference in symptom type between the parents, is conferred by the larger MstII fragment, is consistent with reports that the major determinants of symptom production are located in ORF VI (Schoelz et al, 1986;Baughman et al, 1988). The necrosis seen in W/CSinoculated plants, more extensive than caused by either parent, is consistent with the suggestion that interactions between different regions of the CaMV genome can produce novel symptom types (Daubert et al, 1984).…”
Section: Discussionsupporting
confidence: 74%
“…The observation that the ability to cause rugosity, the only clear difference in symptom type between the parents, is conferred by the larger MstII fragment, is consistent with reports that the major determinants of symptom production are located in ORF VI (Schoelz et al, 1986;Baughman et al, 1988). The necrosis seen in W/CSinoculated plants, more extensive than caused by either parent, is consistent with the suggestion that interactions between different regions of the CaMV genome can produce novel symptom types (Daubert et al, 1984).…”
Section: Discussionsupporting
confidence: 74%
“…Using transgenic plants containing integrated multimers of TGMV A and B, we have shown that TGMV functions are divided between the two genome components and confirmed that both DNAs are essential for productive infection (Rogers et al, 1986). Transgenic plants have also been used successfully to identify the single genes for the movement protein of tobacco mosaic virus (Deom, Oliver, and Beachy, 1987), a protein that may be involved in cauliflower mosaic virus symptom production (Baughman, Jacobs, and Howell, 1988), and the replicase of alfalfa mosaic virus (van Dun, van Vloten-Doting, and BOI, 1988). We describe here the construction of transgenic tobacco plants that contain the leftward open reading frames of TGMV A under the control of the cauliflower mosaic virus (CaMV) 35s promoter.…”
Section: Introductionmentioning
confidence: 96%
“…P6 is the major pathogenicity determinant for CaMV (Daubert et al, 1984;Baughman et al, 1988;Stratford and Covey, 1989;Zijlstra and Hohn, 1992) and was recently shown to be a suppressor of RNA silencing (Love et al, 2007). In addition, P6 also functions as an avirulence determinant, as it has been shown to be responsible for eliciting a hypersensitive response in Nicotiana edwardsonii and Datura stramonium, as well as nonnecrotic resistance in Nicotiana bigelovii and Arabidopsis (Arabidopsis thaliana) ectotype Tsu-O (Daubert et al, 1984;Schoelz et al, 1986;Wintermantel et al, 1993;Agama et al, 2002).…”
mentioning
confidence: 99%